Continuity or Rupture? Further Thoughts on the ‘Classical Revolution’ (2500+ Years after Salamis) - Stewart, Andrew (Journal of Greek Archaeology, 2021)
In the last half-dozen years, the early fifth-century BC ‘Classical Revolution’ in Greek sculpture and painting has become ‘hot’ again. Did it develop gradually, incrementally, and logically out of the Archaic, or emerge quite suddenly (if so, when?), or involve some combination of both? Since chronology drives the debate, as usual in the study of ancient material culture, to restate some basic principles seems appropriate.